PENGARUH PROFITABILITAS, LIKUIDITAS, DAN SOLVABILITAS TERHADAP OPINI AUDIT GOING CONCERN - Nely Anggraini; Herlina Pusparini; Robith Hudaya (Jurnal Aplikasi Akuntansi, 2021)
This study aims to test the effect of profitability, liquidity, and solvency to the audit opinion going concern. Testing was conducted at 125 sample of the company service sector listed on the Indonesia Stock Exchange (IDX) in the 2015-2019. This type of research is associative research that aims to know the effect of profitability, liquidity, and solvency on audit opinion going concern. The type of research data is quantitative data with secondary data obtained from the company’s financial statements accessed through the website official IDX and each sample company. Data processing techniques using logistic regression analysis methods with IBM SPSS software application 25. The result of this study indicate that profitability and liquidity have not significant effect on the audit opinion going concern, while but solvency has an significant effect on the audit opinion going concern. Research results can implications for corporate managers, auditors, investors, and creditors in making decisions and analyzing financial condition of the company that was threatened to get audit opinion going concern where it can establish the right policy for the condition.